2018
DOI: 10.1002/pca.2808
|View full text |Cite
|
Sign up to set email alerts
|

Separation of nine novel triterpene saponins from Camellia japonica seeds using high‐performance countercurrent chromatography and reversed‐phase high‐performance liquid chromatography

Abstract: Introduction Camellia japonica L. (Theaceae) is an evergreen shrub, which is cultivated as a popular ornamental tree in Korea, China, and Japan and its seeds have been used as a source of cooking oil, in cosmetics and as a traditional medicine. Intensive phytochemical works have revealed that oleanane‐type saponins are the characteristic compounds of the seeds of C. japonica. Objective The purpose of the present study is to isolate and determine oleanane‐type saponins from C. japonica using high‐performance co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…The exact anti-bacterial compound from the EO was purified by using preparative HPLC using n-Hexane as a active solvent ( Rho et al, 2019 ). After purification, the purified EO material was analyzed by analyticle HPLC for identified the different groups of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The exact anti-bacterial compound from the EO was purified by using preparative HPLC using n-Hexane as a active solvent ( Rho et al, 2019 ). After purification, the purified EO material was analyzed by analyticle HPLC for identified the different groups of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The orthogonality of CCC-HPLC was calculated to be 52.23% using Eqs. (1) and (2). The results demonstrated that the combination of RP CCC with HPLC in 2D separations was a powerful approach for the separation of mixtures containing various categories of compounds.…”
Section: Off-line Comprehensive 2d Separation Of Polygonum Cuspidatummentioning
confidence: 89%
“…products including chemical components, peptides and polymers [1][2][3][4][5][6]. It has been widely used for preparative separation of effective components from natural products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a continuous liquid–liquid partition chromatography method, complications of liquid–solid chromatography such as irreversible adsorption, low recovery, and deactivation or loss of activity of sample can be effectively eliminated due to lack of solid support matrix . Thus, HSCCC has been widely used for the separation and purification of active components from natural products, albeit, it is a big challenge to separate all target components directly from crude extract in a single run. Therefore, the stepwise elution mode was introduced into HSCCC separation to address this problem .…”
Section: Introductionmentioning
confidence: 99%